2012
DOI: 10.1029/2012ja017926
|View full text |Cite
|
Sign up to set email alerts
|

MESSENGER observations of a flux‐transfer‐event shower at Mercury

Abstract: [1] Analysis of MESSENGER magnetic field observations taken in the southern lobe of Mercury's magnetotail and the adjacent magnetosheath on 11 April 2011 indicates that a total of 163 flux transfer events (FTEs) occurred within a 25 min interval. Each FTE had a duration of $2-3 s and was separated in time from the next by $8-10 s. A range of values have been reported at Earth, with mean values near $1-2 min and $8 min, respectively. We term these intervals of quasiperiodic flux transfer events "FTE showers." T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 100 publications
(155 citation statements)
references
References 52 publications
10
145
0
Order By: Relevance
“…These fluctuations grew in amplitude as MESSENGER approached cusp latitudes similar to those seen in the other three DDM passes in Figures 9d, 9f, and 9h. These large-amplitude, several second-long structures are flux transfer event (FTE)-type magnetic flux ropes Slavin et al, 2012). These large-amplitude, several second-long structures are flux transfer event (FTE)-type magnetic flux ropes Slavin et al, 2012).…”
Section: Ddm Flux Transfer Eventsmentioning
confidence: 99%
“…These fluctuations grew in amplitude as MESSENGER approached cusp latitudes similar to those seen in the other three DDM passes in Figures 9d, 9f, and 9h. These large-amplitude, several second-long structures are flux transfer event (FTE)-type magnetic flux ropes Slavin et al, 2012). These large-amplitude, several second-long structures are flux transfer event (FTE)-type magnetic flux ropes Slavin et al, 2012).…”
Section: Ddm Flux Transfer Eventsmentioning
confidence: 99%
“…Plasmoid chains are highly dynamic configurations: plasmoids can rapidly grow by coalescence [4], bounce [5,6] and eject smaller plasmoids [7]. Observational studies revealed the presence of multiple plasmoids in planetary magnetospheric environments [8][9][10][11]. In addition, the possible presence of plasmoid chains has been suggested in the solar corona [12].…”
Section: Introductionmentioning
confidence: 99%
“…FTEs [Slavin et al, 2008[Slavin et al, , 2012bImber et al, 2014]. FTEs are created as 439 reconnection occurs between the IMF and planetary magnetic field at multiple 440 dayside X-lines.…”
Section: Flux Transfer Events 437mentioning
confidence: 99%